'Tribalism', identity fusion and football fandom in Australia: the case of Western Sydney. (3rd April 2021) - Knijnik, Jorge; Newson, Martha
ABSTRACT: Processes of group formation and social identity are key to understanding human behaviour in social domains. In football, 'ultras' groups are currently considered the most visible style of fandom across the football world. By binding individuals together, these groups create new social identities that make them an ideal context for understanding how people behave within group contexts. This paper employs identity fusion theory to analyse a one-year study of the Red and Black Bloc (RBB), an ultras formation in Western Sydney, Australia. With data collected using active interviews, online surveys, participant observation in football stadiums and fans' online forums, the paper discusses the set of circumstances that bought the RBB together as a cohesive unit. It concludes with a set of recommendations to Australian football administrators and beyond, offering a comprehensive view of fans' tribal behaviour and how to make the most of these findings for the betterment of their emergent leagues.